1988
DOI: 10.1055/s-2006-962343
|View full text |Cite
|
Sign up to set email alerts
|

Phorbol Diester Constituents of Croton Oil: Separation by Two-Dimensional TLC and Rapid Purification Utilizing Reversed-Phase Overpressure Layer Chromatography (RP-OPLC)

Abstract: Fourteen known phorbol diester constituents of Croton tighum L. seed oil (croton oil) have been separated by a two-dimensional thin-layer chromatographic (2D-TLC) technique using different sorbent layers on the same plate. After a preliminary purification step using low-pressure liquid chromatography, reversed-phase overpressure liquid chromatography (RP-OPLC) has been shown to be potentially useful for the rapid preparative purification of these toxins. The identity of the major croton oil phorbol diesters wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 10 publications
1
18
0
1
Order By: Relevance
“…1) being short-chain esters of phorbol and 4-deoxy-4a-phorbol, respectively. However, we have found that the individual homologs within the separated A-and B-factor groups will separate by two-dimensional TLC, if a second reversed-phase phase-bonded silica gel layer is used (Erdelmeier et al 1988). 1), which are monoesters (Marshall and Kinghorn 1984).…”
Section: Phorbol Ester Constituents Of Croton Oilmentioning
confidence: 97%
See 2 more Smart Citations
“…1) being short-chain esters of phorbol and 4-deoxy-4a-phorbol, respectively. However, we have found that the individual homologs within the separated A-and B-factor groups will separate by two-dimensional TLC, if a second reversed-phase phase-bonded silica gel layer is used (Erdelmeier et al 1988). 1), which are monoesters (Marshall and Kinghorn 1984).…”
Section: Phorbol Ester Constituents Of Croton Oilmentioning
confidence: 97%
“…All of these minor constituents were found to be diesters, with the exception of compounds 22, 23, and 27 ( Fig. We have also developed a reversed-phase OPLC method suitable for the rapid separation of many of the known long-and short-chain phorbol esters of croton oil (Erdelmeier et al 1988). Phorbol esters occur in a combined yield of over 1 % w/w in croton oil, with the most abundant and also most potent biologically active compound in this series being 12-0-tetradecanoylphorbol 13-acetate (TP A, 3) (Hecker and Schmidt 1974).…”
Section: Phorbol Ester Constituents Of Croton Oilmentioning
confidence: 99%
See 1 more Smart Citation
“…In the fully off-line mode, the isolation of separated zones can be achieved by scraping bands from the adsorbent layer followed by elution of the isolated materials, similar to conventional preparative layer chromatography. Phorbol diester constituents of croton oil were isolated by off-line OPLC separation followed by extraction and chemical ionization mass spectrometry for identification [76].…”
Section: Preparative Applicationsmentioning
confidence: 99%
“…In the off-line OPLC method, the steps of operation after development are similar to those of conventional TLC methods: drying, scraping of the sorbent layer, elution, and crystallization. Phorbol diester constituents of croton oil were identified by off-line OPLC separation followed by extraction and chemical ionization mass spectrometry (CI-MS) (90). The on-line method is more effective for preparative applications because time-consuming scraping and elution can be eliminated.…”
Section: B Preparative Applicationmentioning
confidence: 99%